Εξ αποστάσεως σχολική εκπαίδευση και μετασχηματισμός δυσλειτουργικών αντιλήψεων: Εκπαιδευτικό σενάριο με θέμα τη στάση απέναντι στην τεχνολογία - Χρήστου Μαρία (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2022)
The special conditions created due to the COVID-19 pandemic have repeatedly led the educational community to suspend the traditional classroom since March 2020, which has created new challenges for both teachers and pupils. The violent transition from traditional classroom to distance school education has created new data for teachers who have been forced to deal with, without previous experience, appropriate preparation and training, even adequate infrastructure in technological equipment in their vast majority (Ιωακειμίδου, et.al., 2021). The objectively difficult educational conditions that were created, worked for a large part of the teachers as a disorienting dilemma (Mezirow, 1991a). Many of them were confronted with their own dysfunctional perceptions concerning learning, the choice of teaching methods and techniques, the need to support students in order to participate in the educational process, their role as teachers in the distance education. According to Illeris model of three dimensions of learning (2016), every learning process contains of three dimensions: the content dimension, which concerns what is learnt, namely the knowledge, understanding and skills, the acquisition dimension, which covers motivation, emotion and volition, and the interaction dimension of learning, which concerns the way the individual interacts with his/her social and material environment, both on the close, social level, i.e. in a classroom, and on the general societal level. Even in the context of distance school education, the three dimensions of learning need to be taken into account by teachers and govern the educational process. Meanwhile, students should be adequately supported in order to develop specific horizontal skills, such as critical thinking, so that later as adults they will be able to deal with the ill-structured problems of their daily lives (King και Kitchener, 1981, 1994), but also to be able to cope with the multiple demands of the roles they will take on in society, as Kegan mentions (1994). For this reason, they need to be involved from an early age in processes of transformation of potentially dysfunctional points of view expressed in issues that they have experience, in order to develop gradually a more emancipatory way of thinking (Κόκκος, 2017β). This article presents an educational scenario which is based on the application of the method “Transformation Theory in Educational Practice” (Kokkos, 2017α) to primary school students, in the context of distance education, on the subject of pupils’ attitude towards technology. This method utilizes the three dimensions of learning and aims to transform pupils’ dysfunctional perceptions into topics which they have experience. The educational objectives are the following: At the level of knowledge: Pupils to know technological achievements of the past and present. To know ways of utilizing modern technological means. To realize that not all people nowadays have access to modern technological means and the internet. At the skill level: Pupils to utilize modern technological means (i.e. internet, distance learning platforms). To approach critically and creatively the issue of utilizing technological means in our lives. To cultivate aspects of their critical reflection about the dangers of using the internet. At the level of attitudes: To develop a positive attitude towards the use of technology, realizing the benefits and risks associated with its use. The method “Transformation Theory in Educational Practice” consists of five stages. Stage One: The teacher detects the dysfunctional perceptions of the pupils. Stage Two: The pupils express their ideas and the teacher defines and prioritizes the targets of transformation. Stage Three: The teacher organizes the transformational strategy. The positive elements of the teaching content are utilized and enriched, while alternative activities can be used. Stage Four: The teachers and the pupils reflect on their educational experience. Stage Five: The teacher discusses with the pupils specific actions aiming at the continuance of the process of transformation. Considering that the process of transforming perceptions on an issue is a demanding and time-consuming process in both traditional classroom and distance school education, teachers need to prioritize properly the objects of transformation, taking into account the pupils’ perceptual abilities, the available time, the emotional ambience of the classroom, the possible resistances that will arise from the pupils during the transformational process, their own abilities and established perceptions, whether the didactic object they are called to teach is related to the objects of transformation. At the same time, the activities planned by the teachers should involve actively the pupils in the educational process and aim at cultivating aspects of their critical reflection and other horizontal skills for lifelong learning, such as creativity and empathy. Besides, they also need to be based on the cooperative learning approach and to stimulate pupil cooperation, communication, as well as the development of democratic dialogue. Individual and overall feedback should be provided frequently and pupils should have the opportunity to evaluate both themselves and the educational process. However, the inclusion of particular methods which aim at transforming pupils’ stereotypes into everyday teaching practice is related both to the fact that teachers themselves have developed sufficiently their critical reflection in order to deal with their well-established personal perceptions about learning, but also with the type of training they have received, in order to improve gradually the quality of their teaching in the context of traditional classroom and distance school education. The structure of the article is as follows. Initially, reference is made to basic principles of distance school education and the role of the teacher. Next, special reference is made to the three-dimensional model of learning by Illeris (2016), as well as the importance of involving students in processes of transformation of their stereotypes. Then, the method “Transformation Theory in Educational Practice” is presented, through a specific example of its application in the context of distance education, lasting 7 teaching hours, to Primary school pupils of the 4th Grade, on the subject of pupils’ perceptions towards technology. Afterwards, there is a discussion about the results of the application of the method in the specific case and its utilization as a means of transforming the possible stereotypical views of the pupils. Throughout the text of this article, one gender is used, for the sake of economy of speech, without referring to any discrimination based on gender.